Original paperAtopic dermatitis is a serious health problem in Poland. Epidemiology studies based on the ECAP study - Sybilski, Adam J.; Raciborski, Filip; Lipiec, Agnieszka; Tomaszewska, Aneta; Lusawa, Adam; Samel-Kowalik, Piotr; Walkiewicz, Artur; Krzych, Edyta; Komorowski, Jarosław; Samoliński, Bolesław (Advances in Dermatology and Allergology/Postępy Dermatologii i Alergologii, 2015)
Introduction: Global epidemiological studies have revealed considerable geographical differences in prevalence of atopic dermatitis (AD). Aim : To present the epidemiology of AD, risk factors and co-occurrence of allergic diseases in the Polish population. Material and methods: The present paper is a part of the Epidemiology of Allergic Disorders in Poland study. We studied 22 703 participants by ECRHS/ISAAC questionnaire; 18 617 (53.8% female, 24.2% 6–7 y.o., 25.4% 13–14 y.o., 50.4% 20–44 y.o.) completed questionnaires were accepted. Four thousand seven hundred and eighty-three participants (25.7%) have undergone a medical examination. Results: Atopic dermatitis was diagnosed in 3.91% (6–7 y.o. 5.34%, 13–14 y.o. 4.3%, adults 3.02%), more often in females (OR = 1.52; 95% CI: 0.56–0.77), in the cities (OR = 2.23; 95% CI: 1.61–3.09), in mothers (OR = 2.07; 95% CI: 1.72–2.48) and fathers (OR = 2.00; 95% CI: 1.61–2.49) with atopy, higher education (OR = 1.61; 95% CI: 1.11–2.32) and economic status (OR = 1.35; 95% CI: 1.04–1.74). The highest prevalence was found in Katowice (4.89%) and lowest in rural areas (1.9%). Coexisting AD and allergic rhinitis (AR) was found in 26.17%, AR and asthma in 9.09% and AD, AR and asthma in 14.6%. Atopic dermatitis was diagnosed by allergologists in 6.5% (6–7 y.o. 8.7%, 13–14 y.o. 9.0%, adults 3.6%). Most diagnoses were made in Poznan (16.76%) and smallest in rural area (3.67%). 78.8% of subjects were diagnosed with AD for the first time although they had earlier experienced its symptoms. Conclusions : Atopic dermatitis prevalence in Poland is below the mean rate for Europe, but the risk factor profile is similar to other countries. Atopic dermatitis is more frequent in well-educated females with atopic parents and high socioeconomic status and who live in a city.